Transforming the Event Industry: The Role of AR, VR, and Emerging Technologies in Event Management - Bisht, Ajay; Bhatt, Pradeep (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2025)
The event management industry is transforming due to the rapid integration of emerging technologies such as Augmented Reality (AR) and Virtual Reality (VR). These innovations are significantly impacting various operational aspects, including strategic planning, attendee engagement, and service delivery. This study aims to explore the evolving role of AR and VR in enhancing event experiences and improving decision making efficiency. Employing a mixed-methods approach, the research combines quantitative surveys of event planners, observational studies comparing traditional and tech integrated events, and qualitative interviews with attendees and key stakeholders. The findings indicate substantial improvements in event outcomes, including a 30% increase in strategic planning effectiveness, a 17.5% boost in attendee engagement, and a 28.9% enhancement in decision-making processes. The results underscore the potential of immersive technologies to revolutionize event execution and knowledge dissemination. The study contributes to the growing body of literature on technological innovations in events, offering practical implications for event professionals seeking to leverage AR and VR for more immersive and efficient event experiences.